COMPARISON OF MARGINAL BONE TISSUE RESORPTION DURING SINGLE-STAGE AND TWO-STAGE IMPLANTATIONS (Conferencea, 2022)
A dental implant is one of the best options for restoring aesthetics and function. The high success rate of these treatments is due to some considerations such as case selection, choice of implant system and surgical techniques. One-stage or two-stage surgical approaches are routine surgical treatments for dental implants. The minimum rate of bone loss around implants is the most important criterion for evaluating the success of implantation, which can be affected by various surgical methods.